Strength and Micromechanism Analysis of Microbial Solidified Sand with Carbon Fiber - Rongkang Qiu; Huawei Tong; Meixiang Gu; Jie Yuan (Advances in Civil Engineering)
Microbially induced calcite precipitation (MICP) is an effective and ecofriendly technology that utilizes the microbes-induced mineralization to improve foundation soils of the transportation infrastructure. The carbon fiber can be used along with the MICP in order to reduce the brittleness of microbial solidified soil. This paper investigated the strength of carbon fiber-reinforced sand with different mass fractions through a series of unconfined compression tests. The effect of fiber content on the solidification of carbon fiber-reinforced sand was quantitatively analyzed using calcium carbonate content test and penetration test. The microsolidification mechanism was investigated by micrographs from the optical and scanning electron microscope (SEM). The test results showed that unconfined compressive strength generally increased first and then decreased with the increase of the fiber content. The optimal fiber content in the silica and calcareous sand was 0.2% and 0.1%, respectively. The bulging deformation of the fiber-reinforced sand sample was gradually developed along with the fiber breakage during loading.